THE ROLE OF RECREATIONAL BODYBUILDING IN ALLEVIATING PSYCHOLOGICAL STRESS AMONG MIDDLE SCHOOL STUDENTS - Ahmed Sahouane (International Journal of Innovative Technologies in Social Science, 2024)
The study aimed at verifying the effect of the recreational activity (bodybuilding) in the reduction of the psychological pressures among the pupils of the final secondary level (Baccalaureate). And the sample of the research was… we had relied in carrying out the research on the questionnaire sheet. The results came to show a medium positive effect of the practice of the recreational activities inside the bodybuilding halls, where these pressures were reduced in a clear way. And the previous studies have also shown a concordance with these same results, emphasizing the importance of the sport activities in the improvement of the psychological adjustment and in the reduction of the tension. The study finally concluded to the necessity of encouraging the pupils for practicing the sport activities outside the school, and also to support the educational institutions for providing suitable sportive environments.